The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1159/000360288
|View full text |Cite
|
Sign up to set email alerts
|

Frontomaxillary Facial Angle Measurement in Trisomy 21 and Euploid Fetuses: Two- and Three-Dimensional Assessment during Routine First Trimester Screening

Abstract: Objective: To assess 2D and 3D frontomaxillary facial angle (FMFA) measurements in euploid and trisomy 21 fetuses. Materials and Methods: Over a 2-year period, women with singleton pregnancies attending a private prenatal screening and diagnosis practice in Sydney, Australia, were invited to participate in this study where 2D images and 3D volumes of the fetal face were collected during routine first trimester screening. In pregnancies where trisomy 21 was confirmed, FMFA measurements were performed in 2D and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
(47 reference statements)
1
6
0
Order By: Relevance
“…We have shown that retrospectively collected data has similar patient age, fetal size and median frontomaxillary facial angle to the prospectively collected data, confirming the utility and accuracy of 2D retrospective frontomaxillary facial angle measurements performed on trisomy 21 fetuses, provided that the stored images are of sufficient quality and have appropriate anatomical landmarks for accurate caliper placement. Furthermore, the frontomaxillary facial angle measurements of trisomy 21 fetuses in retrospectively assessed 2D images are larger than those of the euploid fetuses, in accord with our findings in the prospectively collected trisomy 21 cohort and with the main body of literature …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We have shown that retrospectively collected data has similar patient age, fetal size and median frontomaxillary facial angle to the prospectively collected data, confirming the utility and accuracy of 2D retrospective frontomaxillary facial angle measurements performed on trisomy 21 fetuses, provided that the stored images are of sufficient quality and have appropriate anatomical landmarks for accurate caliper placement. Furthermore, the frontomaxillary facial angle measurements of trisomy 21 fetuses in retrospectively assessed 2D images are larger than those of the euploid fetuses, in accord with our findings in the prospectively collected trisomy 21 cohort and with the main body of literature …”
Section: Discussionsupporting
confidence: 91%
“…Figure 2B represents the overlaid caliper placement for frontomaxillary facial angle measurement. The data collected was then compared with the 2D prospective data collected by the same authors from trisomy 21 fetuses ( n = 22) and euploid fetuses ( n = 250).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations